OPTIMALISASI SUMBER DAYA MASYARAKAT DAN SUMBER DAYA ALAM DALAM BENTUK NUGGET SEBAGAI OLEH-OLEH KHAS PEKON WAY NIPAH - Sosmiarti Sosmiarti; Putri Arif Rezda; Nidya Nur Syafiqoh; Wirdha Listiani; Febriansyah Putra Djaya Indra; Ana Masykurah; Riki Wahyudi; Tika Mazda (BULETIN ILMIAH NAGARI MEMBANGUN, 2018)
Pekon Way Nipah area is an area that has great potential in tourism, because there are Teluk Semaka in the East and Bukit Barisan Selatan National Park (TNBBS) in the West. Pekon Way Nipah is a Pekon located in Pematang Sawa sub-district, Tanggamus district. Having a tourism potential in the form of a bay makes Pekon Way Nipah has great potential in the field of fisheries, but the fact that occurs in Pekon How to produce agricultural products, is not optimal by the community, and even for the economic community. The purpose of product optimization in the form of nuggets as a typical products is that the community has a role to support the economy with the great potential possessed by Pekon. The method is training and socialization community members of Way Nipah. The results that have been issued are the creation of nuggets with complete packaging as souvenirs of the typical products method, as well as recipe books that have been made for the community. The report of this community empowerment is PKK mothers and the community knows how to make nuggets and has their own products.